2012
DOI: 10.1016/s2255-4971(15)30128-2
|View full text |Cite
|
Sign up to set email alerts
|

Safe Localization for Placement of Percutaneous Pins in the Calcaneus

Abstract: Objective: To determine the areas presenting risk in six zones of the calcaneus, and to quantify the risks of injury to the anatomical structures (artery, vein, nerve and tendon). Method: Fifty-three calcanei from cadavers were used, divided into three zones and each subdivided in two areas (upper and lower) by means of a longitudinal line through the calcaneus. The risk of injury to the anatomical structures in relation to each Kirschner wire was determined using a graded system according to the Licht classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Due to the unique bone morphology accurate screw placement is a challenge. The entry points, screw paths trajectories and screw lengths depends on the type of the fracture and the direction of dislocated fragments (12,13,14). The aim is to place the screws in such way to create a support in the dense spongy bone and to ensure stable fixation of the posterior facet.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unique bone morphology accurate screw placement is a challenge. The entry points, screw paths trajectories and screw lengths depends on the type of the fracture and the direction of dislocated fragments (12,13,14). The aim is to place the screws in such way to create a support in the dense spongy bone and to ensure stable fixation of the posterior facet.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Labronici et al 20 , the calcaneus was divided into six areas, to try to replicate a fracture of the calcaneus that would be fixed using six 2 mm Kirshner wires. The three most medial and proximal zones of the calcaneus (IA, IB and IIA) presented the most significant risks of injury to arteries, veins and nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have attempted to divide the surfaces of the calcaneus into zones according to increasing risk of injury to neurovascular and tendinous structures [16][17][18][19][20] but have yet to come to a clear agreement. It has been suggested by Labronici et al that vascular structures found superficially to the anteromedial surface of the calcaneus are at high risk of damage during wire fixation performed via the lateral aspect of the hindfoot 20 .…”
Section: Introductionmentioning
confidence: 99%